Environmental regulation: Lessons for developing economies in Asia - Jinhua Zhao (Asian Development Bank Institute (ADBI), 2019)
Developing countries in Asia face a variety of environmental challenges. Although environmental economics grew mostly out of the experience of developed countries, decades of environmental economics research offer important and useful lessons for environmental regulation in developing countries in Asia. We synthesize the theoretical and empirical literature on environmental regulation and highlight important insights on formal regulation such as taxes, standards, and tradable permits, as well as on informal regulation such as information and voluntary approaches. We also discuss directions for future research.
Keywords: Q58; O13; 330; pollution tax; tradable emission permits; command-and-control policies; Coase bargaining; informal regulation; imperfect enforcement